2022
DOI: 10.1111/os.13318
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Computed Tomography Analysis of Femoral Head Necrosis After Long‐Term Internal Fixation for Femoral Neck Fracture

Abstract: Objective To analyze necrotic femoral head after long‐term internal fixation for femoral neck fractures using micro‐computed tomography (CT) for bone histomorphometry. Methods The experimental group included six patients (two men and four women; mean age 62.00 ± 9.36 years) who underwent hip arthroplasty at 47.67 ± 14.22 months after internal fixation. Surgery was performed because of femoral head necrosis after femoral neck fracture between October 2018 and October 2020. The control group included three patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Our previous research noted a significant degree of sclerosis surrounding the femoral screw path, as observed on computed tomography scans after prolonged retention of the internal fixation implant post-FNF surgery 7 . This densely distributed region is referred to as sclerotic cancellous bone (SCB).…”
Section: Introductionmentioning
confidence: 79%
“…Our previous research noted a significant degree of sclerosis surrounding the femoral screw path, as observed on computed tomography scans after prolonged retention of the internal fixation implant post-FNF surgery 7 . This densely distributed region is referred to as sclerotic cancellous bone (SCB).…”
Section: Introductionmentioning
confidence: 79%
“…While the advantages of screw path implants in mechanics have been mentioned above, a study demonstrated that the presentation of a sclerotic region around the screw path increases the risk of femoral head collapse due to stress concentration and prevents sclerosis formation from becoming critical [ 13 ]. We believe that the clinical outcomes of the patients can be improved by selecting appropriate implant materials and optimizing surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Previously our team has determined that regardless of whether implants are removed, there is risk of collapse of the femoral head, for as long as sclerotic bone around the screw paths persist following healing of FNFs. In addition, as we concluded in a clinical work, years after removal of the internal fixation material, no effective tissue filling develops in the screw paths [ 13 ]. Preventing the formation of osteosclerotic areas is critical.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, trabecular plates were more involved in bone remodeling and played a leading role in sustaining the external load. Therefore, trabeculae around the screw may be partially converted from rods into plates, concentrating and thickening to form plate sclerotic bone, to withstand a larger external load [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since little information was available on the sclerotic region around the screws, we used micro-CT to assess the changes in bone microstructure in the different regions of femoral head specimens that had undergone osteonecrosis [ 12 ]. Samples were divided into necrotic collapse, sclerotic, and relatively healthy regions (as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%